(untitled) (Scottish Historical and Archaeological Internet Reports, 2007)
The excavations have revealed some of the physical remnants of what may have been an extensive and prolonged series of events that comprised the funerary ritual. Cremation, burial of selected remains and the construction of a monument are the most obvious archaeological parts of these events.